Coupling Effect of Air Flow Rate and Operating Conditions on the Performance of Electric Vehicle R744 Air Conditioning System - Anci Wang; Jianmin Fang; Xiang Yin; Yulong Song; Feng Cao; Paride Gullo (Applied Sciences, 2021)
The air flow rate on the gas cooler side is one of the key parameters affecting the performance and running safety of transcritical CO2 electric vehicle air conditioning systems. After experimentally analyzing the effects of the air volume flow rate in the gas cooler on the cycle parameters and system performance, a novel method to evaluate the optimal air flow rate was proposed. In addition, the effect of the gas cooler air volume flow rate on the key performance parameters of the system (e.g., optimal discharge pressure) was explored. Finally, the coupling effects of the compressor speed, ambient temperature and optimal air flow rate on the system performance was also exhaustively assessed. It was found that as the discharge temperature, the CO2 temperature at the gas cooler outlet and the discharge pressure did not vary more than ±2%, the corresponding gas cooler air volume flow rate was optimal. For the single-row and dual-process microchannel evaporator used in this work, the recommended value of the optimal gas cooler air volume flow rate was 2500 m3·h−1. The results could provide reference for the fan speed design of electric vehicle CO2 air conditioning systems, especially for the performance under idling model.